THEORETICAL RESEARCHES AND PROBLEMS OF REALIZATION OF SOCIAL RESPONSIBILITY OF BUSINESS - N. V. Orlova (Ринкова економіка: сучасна теорія і практика управління)
The purpose of this article is to analyze the conceptual foundations of social responsibility of business and the problems of implementation of socially responsible practices in Ukraine.  The approach is to present the importance of this activity, a review of the evolution of the corporate social responsibility concept, the main directions and difficulties of the implementation of these activities in practice.